Christ-Siemens-Touraine syndrome: A rare case report - Anoop Kumar; Priya Thomas; Therraddi Muthu; Maya Mathayoth (Wolters Kluwer Medknow Publications, 2019)
Christ-Siemens-Touraine syndrome/hypohidrotic ectodermal dysplasia (HED) is a heterogeneous group of inherited disorders with primary defects in tissues derived from embryonic ectoderm such as hair, tooth, nail, and sweat glands. To date, more than 192 distinct disorders have been described. Here we present a case of 19-year-old female patient that manifested with HED (Christ-Siemens-Touraine syndrome).